2015
DOI: 10.1371/journal.pone.0135816
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Genotype D Isolates Circulating in Chapecó, Southern Brazil, Originate from Italy

Abstract: Hepatitis B virus genotype A1 (HBV/A1), of African origin, is the most prevalent genotype in Brazil, while HBV/F predominates in the other South American countries. However, HBV/D is the most common in the three states of southern Brazil, where ‘islands’ of elevated prevalence, as Chapecó and other cities, have been described. In this study, 202 HBV chronic carriers attending in 2013 the viral hepatitis ambulatory of Chapecó, were investigated. In comparison with previous studies performed in the same ambulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 39 publications
6
19
1
Order By: Relevance
“…HBV infection is one of the important health problems in Brazil. In South Brazil, recent data indicate that a prevalence rate higher than the average occurs in some cities and regions ( Bertolini et al 2012 , Gusatti et al 2015 ). Caxias do Sul is one of these cities, with 1.6% population positive towards HBsAg ( Menegol & Spilki 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV infection is one of the important health problems in Brazil. In South Brazil, recent data indicate that a prevalence rate higher than the average occurs in some cities and regions ( Bertolini et al 2012 , Gusatti et al 2015 ). Caxias do Sul is one of these cities, with 1.6% population positive towards HBsAg ( Menegol & Spilki 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the southernmost regions have a low HBV prevalence, but the states of Santa Catarina and Paraná were reported to have moderate to high endemicity ( Souto 2016 ). Previous studies have also demonstrated that some specific populations (Italian descendants) contribute to high hepatitis B rates in some regions and cities of South Brazil ( Bertolini et al 2012 , Gusatti et al 2015 ).…”
mentioning
confidence: 97%
“…Another relevant characteristic of the present study was its uniformity in terms of viral genotype. Indeed, it has been previously shown that >95% of the HBV isolates circulating in Chapecó belonged to the same genotype (D) [Gusatti et al, ]. This was a great advantage compared to other studies in which the HBV genotypes involved were not determined or where the patients were infected with different genotypes, which introduced a supplementary variable and might hamper the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected from 345 adults living in Chapecó, state of Santa Catarina, southern Brazil, who were divided into two groups. Group 1 consisted of 196 HBV chronically infected patients attending a viral hepatitis ambulatory [Gusatti et al, ]. One hundred and thirty‐six (69.4%) of them were asymptomatic carriers, 59 (30.1%) were patients with chronic active hepatitis B without cirrhosis, and the remaining one (0.5%) was a cirrhotic patient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation